ISLAMISASI DI TAYANDO KOTA TUAL MALUKU (POLA ADAPTASI RITUAL DAN PERKEMBANGAN KELEMBAGAAN ISLAM) Islamization in Tayando of Tual City Maluku (Pattern of Adaptation Ritual and Development Institutional Islamic) - JAMAIN WARFEWUBUN (IAIN TERNATE, 2017)
AbstractThe aims of this research is to examine the process of Islamization in Tayando of Tual City in Maluku; the system of ritual adaptation in Tayando of Tual City in Maluku, and the development of Islamic Institutions in Tayando of Tual City in Maluku.This research employed historical research where teh writing was conducted though analytic descriptive that relies on written sources or documentation. Data were collected by library research, inteview, and documentation. Technique used for data analysis was source critics, interpretation, and then writing of history.The result of the research show that the process of Islamization in Tayando of Tual City in Maluku is from Datuk Abdullah from Banda Neira trough Seram, Ambon, Kepulauan Kur, Tam, and ends in Tayando. Islamization is also influenced by Kesultanan Ternate and Tidore. However, the influenced of Kesultanan Tidore is more dominan; (ii) the ritual adaptation in Tayando of Tual City in Maluku is the tradition of each district had existed before Islam existed in the district so it gives its own color for Islam. The dominant forms of ritual adaptation in Tayando society in education, and tasauf. The Islamization in Tayando of Tual City in Maluku is through cultural approach, namely adaptive and accomodative with local culture and tradition. The spreading of Islam in Tayando of Tual City is withouth force as well with sword. Hawever, teh spreading of Islam is only through dakwah, meetings as in wedding party or Islamic events; (iii) the development of Islamic institutions in Tayando of Tual City in Maluku are religious institutions in bureaucracy structure, mosques, religius education institution, religius and politic organizations, art anda sport institutions.